Fertility Challenges Facing Women with Early-Stage Endometrial Cancer - Macklon, Kirsten Tryde (Seminars in Reproductive Medicine, 2025)
Young women diagnosed with endometrial cancer may have a fertility wish and may, under certain conditions, be offered fertility-sparing treatment. However, they may also have underlying infertility issues, as anovulation, obesity, polycystic ovary syndrome, and advanced maternal age are often found in women with endometrial cancer or atypical hyperplasia. These fertility issues may hinder pregnancy or prolong the time to pregnancy, in a situation where not much time is allowed to try for a pregnancy. Referral to a reproductive specialist is recommended as early as possible to detect any possible underlying infertility issues that might require assisted reproductive technology once a pregnancy is allowed or may even contradict fertility-sparing treatment. Ovarian reserve testing is a tool used to assess a woman's ovarian reserve, although it cannot, as such, be used to predict the chance of pregnancy. In case of obesity, weight loss is recommended as soon as possible.
Keywords: endometrial cancer; fertility; obesity; ovarian reserve; PCOS